2020
DOI: 10.1186/s12939-020-01200-9
|View full text |Cite
|
Sign up to set email alerts
|

Living or deceased-donor kidney transplant: the role of psycho-socioeconomic factors and outcomes associated with each type of transplant

Abstract: Background Kidney transplant improves patients’ survival and quality of life. Worldwide, concern about the equality of access to the renal transplant wait-list is increasing. In Iran, patients have the choice to be placed on either the living or deceased-donor transplant wait-list. Methods This was a prospective study performed on 416 kidney transplant recipients (n = 217 (52.2%) from living donors and n = 199 (47.8%) from deceased donors). Subjects were recruited from four referral kidney transplant centers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
0
6
0
4
Order By: Relevance
“…Similarly to what happens with large series (Collaborative Transplant Study [ 58 ] and UNOS Register [ 59 ]), it is observed that living-donor kidney transplantation provides better outcomes than deceased-donor transplantation. Besides, it is associated with shorter transplant waiting list period and better early outcome [ 60 ]. We have found that CMV disease represents a risk of death in our population.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to what happens with large series (Collaborative Transplant Study [ 58 ] and UNOS Register [ 59 ]), it is observed that living-donor kidney transplantation provides better outcomes than deceased-donor transplantation. Besides, it is associated with shorter transplant waiting list period and better early outcome [ 60 ]. We have found that CMV disease represents a risk of death in our population.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 31 In this study, we used insurance status as an indicator of socioeconomic status; however, this does not fully reflect differences in access and quality of care. Basiri et al 32 found that better outcomes were associated with living donors and that those of higher socioeconomic and educational status had higher likelihood of living donors. Patzer et al 12 also demonstrated significant racial disparities in preexisting risk factors for poorer allograft survival, such as low socioeconomic status; however, evidence has been found that, in settings where all patients have equal access to and quality of care, Black recipients still suffer worse outcomes than non-Blacks.…”
Section: Discussionmentioning
confidence: 99%
“…Aunque el TRDV se asocia con un período de espera para el trasplante más corto y un mejor resultado en cuanto a supervivencia y calidad de vida, no todas las personas con ERC candidatas a trasplante tienen esta oportunidad 22 . En nuestros análisis, solo el 11,54% de todos los candidatos a receptor de TR evaluados durante el 2020 tuvieron la oportunidad de esta modalidad de tratamiento, siendo realmente efectiva en el 2,80% de los casos y representando el 14,16% de la actividad trasplantadora del centro explorado.…”
Section: Discussionunclassified
“…En la misma línea, la Organización Nacional de Trasplantes (ONT) en España en su "Plan de acción para la mejora de la donación y el trasplante de órganos" 23 identifica ciertas barreras para el TRDV: falta de información a pacientes y familiares sobre el TRDV; complejidad en los trámites legales-administrativos en la donación de vivo; necesidad de mejora en la seguridad y protección del donante vivo; e incompatibilidad donante-receptor. Una de las causas que se apunta está relacionada con el nivel socioeconómico y educativo, encontran- do que aquellas personas con niveles más altos tienen una probabilidad significativamente mayor de tener un cDR 22 . Se han explorado posibles soluciones 24 , entre las que destacan: el desarrollo de una red de pacientes mentores para apoyar y educar a familias y pacientes con ERC para que exploren la posibilidad de un trasplante de riñón de donante vivo desde una perspectiva vivida; políticas de reembolso para cubrir los gastos que se puedan derivar del estudio, la donación y el seguimiento post donación; y la asociación con empresas de seguros para mejorar la eficiencia en el proceso de evaluación de donantes y receptores.…”
Section: Discussionunclassified